2019
DOI: 10.1155/2019/9397578
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Model for Imbalanced Cholera Dataset in Tanzania

Abstract: Cholera epidemic remains a public threat throughout history, affecting vulnerable population living with unreliable water and substandard sanitary conditions. Various studies have observed that the occurrence of cholera has strong linkage with environmental factors such as climate change and geographical location. Climate change has been strongly linked to the seasonal occurrence and widespread of cholera through the creation of weather patterns that favor the disease’s transmission, infection, and the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 53 publications
(58 reference statements)
2
21
0
Order By: Relevance
“…This is an ensemble learning method that fits multiple decision tree classifiers and uses bootstrapping to output a decision averaged over these predictors, to improve prediction accuracy and reduce effects of over-fitting. This approach is consistent with previous literature investigating similar outbreak risk indexes which have demonstrated RF classifiers to be an appropriate method for the application to epidemiological data along with analyses of environmental factors, including for prediction of outbreaks of cholera disease (e.g., [ 35 ]), vector-borne diseases such as dengue (e.g., [ 52 , 53 ]) and malaria (e.g., [ 54 ]), and the avian influenza H5N1 zoonotic disease outbreaks (e.g., [ 55 ]).…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…This is an ensemble learning method that fits multiple decision tree classifiers and uses bootstrapping to output a decision averaged over these predictors, to improve prediction accuracy and reduce effects of over-fitting. This approach is consistent with previous literature investigating similar outbreak risk indexes which have demonstrated RF classifiers to be an appropriate method for the application to epidemiological data along with analyses of environmental factors, including for prediction of outbreaks of cholera disease (e.g., [ 35 ]), vector-borne diseases such as dengue (e.g., [ 52 , 53 ]) and malaria (e.g., [ 54 ]), and the avian influenza H5N1 zoonotic disease outbreaks (e.g., [ 55 ]).…”
Section: Methodssupporting
confidence: 87%
“…A monthly resolution allows for possible incubation periods of V. cholerae and accommodates potential lags between infection incidence and reporting. This resolution has also been used in previous studies, which have reported that the cholera-incidence response range to environmental variables within a week is generally insignificant [ 35 ]. The chlorophyll-a concentration dataset was converted to a logarithmic scale to accommodate the large range of values, spanning three orders of magnitude.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multilayer Perceptron (MPL) and J48 classifier techniques in the Weka tool recently being used in successfully predicting malaria incidents [32][33][34]. Researchers around the globe also used it for prediction of dengue [35][36][37][38] and other public health issues such as Cholera [39], diabetes [40][41][42], heart diseases [43,44].…”
Section: Data Preparationmentioning
confidence: 99%